The Dynamics of Product Quality and International Competitiveness - Mody, Ashoka (IMF Working Papers; Working Paper, 2007)
Despite the appreciation of the exchange rate, the eight Central and Eastern European countries (the CEE-8) that entered the European Union in May 2004 have achieved a decade of impressive export growth, expanding significantly their shares of world markets. Does this mean that the real exchange rate is irrelevant? If not, what other factors compensated for the appreciation to explain the apparently strong competitiveness of these economies? And will these favorable factors continue to power export growth? This paper places in international context the achievements of the CEE-8 and helps more broadly to identify the determinants of international competitiveness. Building from data at the six-digit level of disaggregation, it shows that the CEE-8 made an impressive shift in product quality and in the technological intensity of exports, and that these shifts associated with the structural transformation were also associated with increased market share. The analysis strongly suggests that, when trading in international markets, countries benefit from higher product quality. However, while the structural transformation achieved was valuable in raising market shares, the easy gains from this process may be over.